The theology of the Gospel of Matthew - Luz, Ulrich 1938-2019; Robinson, J. (Cambridge Cambridge University Press, 1995)
Matthew's Gospel is the most significant Jewish-Christian document of the New Testament. For Matthew, the story of Jesus is the underlying tale of his own community, summoned from Israel by the living Jesus and now, following Israel's rejection, sent to the Gentiles. Matthew's Jesus story bears much the same relation to the Matthean community as does the Pentateuch to Israel, hence the profoundly Jewish basis of his theology. This book, first published in 1995, both outlines and elucidates the story told in Matthew's Gospel, emphasising its focal points: the Sermon on the Mount, the miracles, the renunciation of possessions and particularly the theology of judgement by works, an idea which represents both a challenge, in its quest for a church set apart from non-Christians by deeds alone, and a burden, through its traumatic origin in the breach between the Matthean community and the Israelite majority.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible; Bible -- Criticism, interpretation, etc; Bible -- Theology; Bible ; Matthew ; Theology; Bible ; Matthew ; Criticism, interpretation, etc